Comparative Analysis of Hadith Scholarship in the Malay-Indonesian Archipelago: Historical and Methodological Perspectives on the Transformation of Contemporary Islamic Knowledge: (Analisis Komparatif Studi Hadis di Nusantara: Telaah Historis-Metodologis dalam Konteks Transformasi Keilmuan Islam Kontemporer) - Devi Ganis Prameswari; Cermi City Mulyanti; Dadah Sa’adah (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2026)
This study provides a comparative analysis of the development of hadith studies in the Nusantara region, focusing on Indonesia and Malaysia within the context of contemporary Islamic scholarly transformation. The scope of the analysis includes scholarly networks and the transmission of knowledge from the Haramayn, methodological differences between the turath-based approach in Nusantara and the academic systematic approach in Malaysia, as well as the role of educational institutions in integrating the tradition of sanad with digital innovation. Employing a qualitative historical comparative method, the data are derived from curricula, the works of local muhaddithun, and relevant academic literature. The findings indicate that hadith studies in Indonesia are characterized by a sanad-centric orientation through systems of talaqqi and ijazah, whereas in Malaysia they tend to be more analytical and academically structured. Both contexts currently face challenges related to integration with digital technologies, including the use of AI, online databases, and the digitization of kitab kuning. These epistemological differences are not dichotomous but instead reflect methodological diversity that enriches Islamic studies in Southeast Asia. This study underscores the importance of synergy between the approaches of riwayah (transmission) and dirayah (rational analysis) as a foundation for developing integrated curricula in pesantren, universities, and research institutions. Academically, this research offers a new conceptual framework for integrating classical tradition and digital technology in hadith studies.